The motivation and process for developing a consortium‐wide time and motion study to estimate resource implications of innovations in the use of genome sequencing to inform patient care - Hannah G. Hoban; Tiffany A. Yip; Joanna C. Chau; Jeannette T. Bensen; Lauren R. Desrosiers; Candice R. Finnila; Lucia A. Hindorff; Nicole R. Kelly; Frances L. Lynch; Bradley A. Rolf; Hadley S. Smith; Melissa P. Wasserstein; et al. (Wiley, 2024)
Abstract Costs of implementing genomic testing innovations extend beyond the cost of sequencing, affecting personnel and infrastructure for which little data are available. We developed a time and motion (T&M) study within the Clinical Sequencing Evidence‐Generating Research (CSER) consortium to address this gap, and herein describe challenges of conducting T&M studies within a research consortium and the approaches we developed to overcome them. CSER investigators created a subgroup to carry out the T&M study (authors). We describe logistical and administrative challenges associated with resource use data collection across heterogeneous projects conducted in real‐world clinical settings, and our solutions for completing this study and harmonizing data across projects. We delineate processes for feasible data collection on workflow, personnel, and resources required to deliver genetic testing innovations in each CSER project. A critical early step involved developing detailed project‐specific process flow diagrams of innovation implementation in projects' clinical settings. Analyzing diagrams across sites, we identified common process‐step themes, used to organize project‐specific data collection and cross‐project analysis. Given the heterogeneity of innovations, study design, and workflows, which affect resources required to deliver genetic testing innovations, flexibility was necessary to harmonize data collection. Despite its challenges, this heterogeneity provides rich insights about variation in clinical processes and resource implications for implementing genetic testing innovations.